Four new cunaxoidine genera (Acari: Prostigmata: Cunaxidae) and the description of Two new Neotropical species - Den Heyer, Jacob; De Castro, Tatiane M. M. G. [UNESP] (My University, 2009)
In this paper the genus Cunaxoides Baker & Hoffmann, 1948, as delimited by Den Heyer (1979a, 1981b), is revised and divided into five genera, viz. Cunaxoides Baker & Hoffmann, Bunaxella gen. nov., Dunaxeus gen. nov., Funaxopsis gen. nov. and Qunaxella gen.nov.. Two new Neotropical species, Dunaxoides duosetosus and Qunaxella triasetosa are described and figured. Additional southern African material is reported. A key to the genera and species of the new genera of the subfamily Cunaxoidinae is provided. Copyright © 2009. Magnolia Press.
Keywords: Bdelloidea; Cunaxoidinae; Four new taxa; Identification key; Taxonomy